MENGURAI KONFLIK KOREKSI ARAH KIBLAT DI TENGAH-TENGAH MASARAKAT - Jayusman (Jurnal Hukum Islam, 2012)
The accurate Qibla direction has significant contribution to the perfection of Muslim’s praying (shalat). It is very tough to pray with a completely straight position towards the Qibla. In addition, to build a mosque with accurate Qibla direction is not easy. It may have been measured properly but there was a shift in its development. The position of mosque where they were praying may shift a few degrees from the accurate direction of Qibla. Therefore, this paper will discuss the Qibla direction in order to avoid the difficulty in praying.